Control strategy of sideslip perching maneuver under dynamic stall influence - Feroskhan, Mir (2019)
This paper presents a sliding control strategy for executing a sideslip perching maneuver under dynamic stall influence. Perching is a type of aggressive maneuver performed by the avian species to acquire rapid deceleration, which is frequently followed by a precision landing. Due to the high turn rates and rapid changes in aerodynamic angles in the three-dimensional domain, robustness to state perturbations and model inaccuracies is mandatory as it is impossible to develop a completely accurate aerodynamic model for perching that involves many dynamic phenomena and different flow regimes. Based on the optimal trajectory solutions generated through an optimization procedure, sliding mode control is proposed to address the need for robust tracking in the nonlinear, unsteady region of flight dynamics with the inclusion of dynamic stall delay. Performance of the controller is validated under different scenarios involving varying initial spatial and state conditions and state perturbations throughout the course of the perching maneuver.